Cosmic Calligraphy and Character Physiognomy 相字 in Late Imperial China - Wang, Xing (Material religion, 2023)
This paper examines the cultural history of a special divinatory practice in China during the Ming and Qing dynasties (1368–1912): the physiognomy of written characters (sinographs), in which the physical characteristics of written characters are used to ascertain information about the life of the one who writes them. For practitioners of character physiognomy, a written character can foreshadow a person’s fortune because of the cosmology of ubiquitous association, in which sinographs are seen as meaningful pictorial symbols that function as replicas of the material world as well as cosmic extensions of the human body. From the style and configuration of a written character, and even its locus in a particular time and place, specialists could imagine and reconstruct the gestures and bodily form of its writer. Because of this, written characters were conceptualized as replicas of the human body, and could in this way mirror their writer’s fortune.